Cutaneous Myxoma in Broiler Chicken Detected during Slaughtering - Quedi Furian, Thales; Apellanis Borges, Karen; Zottis Chitolina, Gabriela; Patrin Pontin, Karine; Bello Fallavena, Luiz César; Pinheiro do Nascimento, Vladimir; Pippi Salle, Carlos Tadeu; de Souza Moraes, Hamilton Luiz (Acta Scientiae Veterinariae, 2023)
Background: A cutaneous or superficial myxoma is a benign neoplasm of dermal or subcutaneous fibroblast origin. Although rare, it has been previously described in several species, including poultry. It presents as a single node or soft mass with a gelatinous cut surface. Histopathological analysis is essential for diagnosis and to differentiate it from other mesenchymal neoplasms and inflammatory or degenerative processes. Microscopically, it consists of dermal or subcutaneous lobules of plump, stellate, or spindle-shaped, bland-looking cells embedded in a basophilic myxoid matrix. This report describes the pathological findings in a rare case of cutaneous myxoma in a 42-day-old broiler flock. Cases: During ante mortem inspection of a 42-day-old broiler flock at a slaughterhouse under the authority of the Federal Inspection Service (southern Brazil), nodular lesions or encrusted areas with yellow and black areas were observed in the head skin of less than 1% of animals. These lesions, approximately 0.5 cm in diameter, were observed on the comb, in the periocular skin region, and close to the animals’ nostrils. During the breeding period, no health or epidemiological events were observed. Fragments of the lesions in the comb and periocular skin were collected and fixed in buffered 10% formalin. The samples were sent to the laboratory, routinely processed, and stained with hematoxylin and eosin and Alcian blue. Microscopically, the lesions consisted of irregular multifocal proliferation of connective tissue showing spindle cells with poorly demarcated borders and scarce cytoplasm in a slightly basophilic myxoid aspect matrix. The adjacent epidermis is compressed due to neoplastic proliferation. No areas of epithelial hyperplasia or inclusion bodies were observed. According to the pathologic description and considering its descriptive epidemiology, our main clinical suspicion was cutaneous fowl pox, a pathology characterized by the appearance of nodules in regions devoid of feathers. However, the microscopic changes observed were compatible with those described for cutaneous myxomas. In addition, the extracellular matrix was positive for Alcian Blue staining, which is an indicator of myxoma. In the present case, the SIF did not report the same macroscopic lesions in other flocks of the same origin. Discussion: Connective tissue tumors, including myxomas, occur considerably less frequently under field conditions. In addition, these neoplasms are more frequent in mature birds and are not usually described in broilers, as observed in this report. The cutaneous myxoma described in broilers is usually a sporadic neoplasm that does not cause zootechnical losses, as observed in the case report. Its etiology is unknown and has been associated with various factors, such as local trauma and foreign bodies. Some fragments of plant material from the breeding environment were microscopically detected in the encrusted areas, which may indicate previous trauma or a foreign body. Myxoma has been associated with avian leukosis virus (ALV) subgroup A, but SIF did not report the same macroscopic lesions in other flocks of the same breeder hen’s origin in the present case. Furthermore, sporadic connective tissue tumors associated with the virus occur in mature chickens but not in broilers. Myxoma lesions should be considered in the differential diagnosis of other connective tissue tumors and infectious agents that cause lesions in the skin and subcutaneous tissue. Keywords: benign neoplasia, connective tissue tumor, histopathology, poultry.